cDNA Actin Isolated From Pandanus Sp. - Dewi Indriyani Roslim (International Journal of Ecophysiology, 2019)
Actin is one of the reference genes that is often used as an internal control in gene expression analysis. This study aimed to isolate actin cDNA from Pandanus sp originated from Riau. Fresh leaves Pandanus sp. Lake Kajuik, Langgam District, Pelalawan Regency, Riau Province. Isolation of RNA, synthesis of total cDNA, amplification of actin genes used McDowell's designed degenerate primer (PlAc46S-20/PlAc245N-20), electrophoresis, sequencing, and data analysis. Actin cDNA fragments obtained were 353 pb in size, registered at GenBank and encoded 117 amino acids. Actin cDNA fragment consists of two exons and one introne. Specific actin primers from Riau Pandanus sp. can be designed based on sequences obtained for the purpose of analyzing certain gene expressions.